(untitled) (Research, Society and Development, 2022)
The semiarid region has as main characteristics, low precipitation, recurrent droughts, high temperatures and low air humidity. Another point is that most of the soils have a crystalline basement, providing inferior quality to groundwater. In this sense, irrigation is not always viable, as a result of scarce water resources. Hydroponics, however, is soil-independent and requires little water, crops grown in hydroponics are more tolerant to salinity, allowing the use of more saline waters. Given the above, the objective of this research was to verify the initial growth of lettuce Crespa cv. Moana under hydroponic cultivation in the semiarid region under different salinity levels in an automated system with Arduino Uno, where the solution application interval operates as a function of air temperature and humidity. For this purpose, salinity levels 1.5, 2.0, 2.5, 3.0 and 3.5 dS m-1 were used, in a randomized block design with a 5 x 5 factorial scheme in the type system Net Film Technique. It was found that automation at the expense of temperature and humidity promoted greater energy savings, lettuce has better development at the level of 1.5 dS m-1. Therefore, the automation system with Arduino is operational in addition to allowing the association of sensors, and lettuce cv. Moana for the conditions of the experiment does not present satisfactory initial developmentalism above 2.0 dS m-1 due to the deleterious effects of salinity.